Pros and Cons of Vaccine Refusal in Social Media - Cut Meutia Karolina; Irwa Rochimah Zarkasi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
The video of rejection of COVID-19 vaccine by Ribka Tjiptaning, a public figure in Indonesia, has become one of the most popular trending news topics in various media in Indonesia. The purpose of this study is to explore the cyber community beliefs regarding COVID-19 prevention vaccination through Ribka Tjiptaning’s video statement on Instagram and Facebook posts. The research was conducted on Instagram and Facebook comments with a netnographic approach by relying on the selective process theory, the concept of conspiracy, and vaccine hesitancy. Two main themes were identified: pro comments, through statements that support the content on the video, and counter comments, through statements that reject the content on the video.